Mild SARS-CoV-2 Illness Is Not Associated with Reinfections and Provides Persistent Spike, Nucleocapsid, and Virus-Neutralizing Antibodies - Schuler, Charles F.; Gherasim, Carmen; O’Shea, Kelly; Manthei, David M.; Chen, Jesse; Zettel, Cristyn; Troost, Jonathan P.; Kennedy, Andrew A.; Tai, Andrew W.; Giacherio, Donald A.; Valdez, Riccardo; Baldwin, James L.; et al. (Microbiology spectrum, 2021)
This article demonstrates that people who have mild COVID-19 illnesses and produce antibodies are protected from reinfection for up to 6 months afterward. The antibodies that people produce in this situation are stable for up to 6 months as well. Uncertainty exists whether mild COVID-19 confers immunity to reinfection. Questions also remain regarding the persistence of antibodies against SARS-CoV-2 after mild infection. We prospectively followed at-risk individuals with and without SARS-CoV-2 for reinfection and monitored the spike and nucleocapsid antibodies. This prospective cohort study was conducted over two visits, 3 to 6 months apart, between May 2020 and February 2021. Adults with and without COVID-19, verified by FDA EUA-approved SARS-CoV-2 RT-PCR assays, were screened for spike and nucleocapsid antibody responses using FDA EUA-approved immunoassays and for pseudoviral neutralization activity. The subjects were monitored for symptoms, exposure to COVID-19, COVID-19 testing, seroconversion, reinfection, and vaccination. A total of 653 subjects enrolled; 129 (20%) had a history of COVID-19 verified by RT-PCR at enrollment. Most had mild disease, with only three requiring hospitalization. No initially seropositive subjects experienced a subsequent COVID-19 infection during the follow-up versus 15 infections among initially seronegative subjects (infection rates of 0.00 versus 2.05 per 10,000 days at risk [ P = 0.0485]). In all, 90% of SARS-CoV-2-positive subjects produced spike and nucleocapsid responses, and all but one of these had persistent antibody levels at follow-up. Pseudoviral neutralization activity was widespread among participants, did not decrease over time, and correlated with clinical antibody assays. Reinfection with SARS-CoV-2 was not observed among individuals with mild clinical COVID-19, while infections continued in a group without known prior infection. Spike and nucleocapsid COVID-19 antibodies were associated with almost all infections and persisted at stable levels for the study duration. IMPORTANCE This article demonstrates that people who have mild COVID-19 illnesses and produce antibodies are protected from reinfection for up to 6 months afterward. The antibodies that people produce in this situation are stable for up to 6 months as well. Clinical antibody assays correlate well with evidence of antibody-related viral neutralization activity.